Depression, Anxiety, and Acculturative Stress Among Resettled Bhutanese Refugees in Australia. (September 2018) - Lumley, Mia; Katsikitis, Mary; Statham, Dixie
Despite awareness of the difficulties faced by refugees in flight, little is known about their mental health following resettlement. This article investigated rates, predictors, and moderators of anxiety, depression, and acculturative stress among members of the resettled Bhutanese refugee community in northern Queensland. A total of 148 participants (51% male), 18 to 83 years of age, participated in this cross-sectional study. A questionnaire was comprised of bilingual (English–Nepali) versions of the Depression, Anxiety, and Stress Scale (DASS-21; anxiety and depression), the Multidimensional Acculturative Stress Scale (MASS; acculturative stress), Brief-COPE (coping style), Multidimensional Scale of Perceived Social Support (MSPSS; social support), and socio-demographics. Participants reported severe levels of anxiety and moderate levels of depression, and moderate to high levels of acculturative stress. Acculturative stress was a substantive contributor to both depression and anxiety scores. Additional risk factors included the use of maladaptive/avoidant coping styles, age, and education. English language proficiency was strongly protective, as was education to Year 12 and current employment. This research is the first of its kind with this refugee group in Australia, and highlights the longevity and severity of mental health issues that affect Bhutanese refugees resettled in Australia.